Research and Application of CNC Machining Method Based on CAD/CAM/Robot Integration. (9th July 2022) - Yan, Xiangsong
Abstract : In order to improve the effect of intelligent CNC machining, this paper combines the CAD/CAM/Robot integration method to improve the CNC machining method and analyzes the tool path planning method and the path generation algorithm of the five-axis CNC machining machine. Through the tool processing calculation of the representative curved surface, this paper studies the basic theory, process planning, and tool parameter selection of the blade of the representative curved surface in the five-axis CNC machining and generates the blade CNC machining tool path through the simulation software. In addition, this paper analyzes the trajectory of the workpiece through the intelligent processing process and builds an intelligent processing system. Through the statistics of simulation test data, it can be seen that the CNC machining method based on CAD/CAM/Robot integration can effectively improve the intelligence of modern CNC machining and improve the effect of intelligent machining.